FREKUENSI DAN INTENSITAS SERANGAN HAMA DENGAN BERBAGAI PESTISIDA NABATI TERHADAP HASIL TANAMAN BROKOLI (Brassica oleracea L.) - Marhani Marhani (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
The research was conducted of three moon, start in November 2015-January 2016. Location the research in Soekarno-Hatta Road, North Sangata District, East Kutai Regency. The research aimed is determine the yield brocolli plant with botanical pesticides variety in suppress pests attack, determine the frecuention and intencity pests attack on brocolli plant with botanical pesticides variety, and determine the best botanical pesticides type in suppress pests on brocolli plant. The research methode using a Randomized Block Design non factorial with 4 level treatments was used 6 replication. The treatments levels botanical pesticides (A), is namely A0 = without botanical pesticides (control), A1 = botanical pesticides areca nuts extract 40 cc/liter water, A2 = botanical pesticides lemongrass leaves extract 40 cc/liter water, and A3 = botanical pesticides tuba root extrac 40 cc/liter water. The research results showed that, the best treatments at gives botanical pesticides areca nuts extract 40 cc/liter water fresh weight brocolli flowers 0,63 kg, attack frecuention pests 32,48-29,08%, and attack intencity pest 16,16-15,32%.